Present and Future of Personalised Medicine for Endocrine Cancers - Ronchi, Cristina L.; Altieri, Barbara (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Major technological advances in genomics have made it possible to identify critical genetic alterations in cancer, rendering oncology well along the path to "personalised cancer medicine". Thanks to developments in genetics, several mutations and gene rearrangements have been identified in patients with endocrine cancers (e.g., thyroid and adrenocortical carcinoma). In particular, each patient can be considered as a unique, individual one, with unique genetic information. The aim of this Special Issue is to offer an overview of exciting new research in the area of endocrine tumours may set the stage for an innovative personalised management and precision medicine modalities for individualised care.New affordable individual genomic analyses, as well as the opportunity to test new compounds in primary cells may allow a personalised management of patients with endocrine malignancies. This approach may improve the prediction of clinical outcome and therapeutic effectiveness, as well as help to avoid the use of ineffective drugs. However, further efforts are needed to obtain an adjustment of clinical management in patients with endocrine cancers that would rely solely or in great part on genetic information. This Special Issue includes basic, translational, and clinical papers on personalised medicine in endocrine malignancies (i.e., thyroid and adrenal), especially focusing on diagnostic and prognostic biomarkers, as well as novel drug targets or targeted treatments, including eventual clinical trials.